A not of Resurgence of the Cotton Stemborer Sphenoptera gossypii Conte as a Serious Pest in the Irrigated Schemes in Sudan - sebit, ruaa; Abdalla, Tag Elsir E.; Hamad, Abdelmagid A.; Ahmed, Usama M.; Hamad, Abdelmagid A.; Ahmed, Usama M.; Elnour, Omer A.; Salih, Mohamed A. (University of Khartoum Journal of Agricultural Sciences, 2023)
this study was conducted to investigate complaints by farmers in New Halfa Agricultural Corporation (NHAC), Gezira Scheme, Rahad and Suki agricultural schemes about wilting, drying and death of cotton plants during the 2012-2013 season which was the first season for planting the genetically-modified Bt cotton (CN-CO2). A survey was conducted and showed drying and death of young plants and wilting of older ones. A longitudinal section of the stem revealed the presence of white worms of up to 3 cm in length and white shiny pupae, together with coleopteran beetles. The insect was identified as Sphenoptera gossypii. The damage was mainly in the variety CNCO2 but individual plants of the local varieties Hamid, Abdeen and Barakat were also infestation. The highest percentage of infestation was 30% in NHAC while the average infestation was 2% to 3% in the Gezira scheme and was little in the Rahd scheme. The stem borer was a serious pest of cotton in the 1920s and 1903s but as a result of clean-up campaigns and adherence to technical guidelines the local varieties, except Sakel, could survive unaffected. Introduction of the extremely susceptible variety (CNCO2) in large areas in the irrigated schemes, which are plentiful of the pest, led to serious damage to the crop. During October 2012, farmers from New Halfa Agricultural Corporation (NHAC) complained of drying, wilting and death of cotton plants in their fields; the incident was especially higher in the introduced genetically modified Bt cotton variety (CN-CO2) than on the local variety "Hamid". The season (2012-13) ranked first, for commercial planting of the Bt cotton in NHAC, and other irrigated schemes in Sudan. Thus, the Bt cotton was blamed as a causative of the incident. The CN-CO2 seeds